2019
DOI: 10.1158/1541-7786.mcr-18-1372
|View full text |Cite
|
Sign up to set email alerts
|

AKT1E17K Activates Focal Adhesion Kinase and Promotes Melanoma Brain Metastasis

Abstract: Alterations in the PI3K/AKT pathway occur in up to 70% of melanomas and are associated with disease progression. The three AKT paralogs are highly conserved but data suggest they have distinct functions. Activating mutations of AKT1 and AKT3 occur in human melanoma but their role in melanoma formation and metastasis remains unclear. Using an established melanoma mouse model, we evaluated E17K, E40K, and Q79K mutations in AKT1, AKT2, and AKT3 and show that mice harboring tumors expressing AKT1 E17K had the high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…Almost all (94.3%, 33/35) of AKT1 mutations were identified in HR + /HER2breast tumors, with only one typical hotspot mutation. AKT1 E17K is a single amino acid mutation in the pleckstrin homology (PH) domain of the AKT1 protein, which has been reported to function as a carcinogenic driver mutation in breast cancer and other solid cancers [18,19]. In our cohort, breast cancers with AKT1 mutations were significantly associated with positive ER-(P = 0.016) and PR (P = 0.002) but negative HER2-(P = 0.001) status.…”
Section: Discussionmentioning
confidence: 76%
“…Almost all (94.3%, 33/35) of AKT1 mutations were identified in HR + /HER2breast tumors, with only one typical hotspot mutation. AKT1 E17K is a single amino acid mutation in the pleckstrin homology (PH) domain of the AKT1 protein, which has been reported to function as a carcinogenic driver mutation in breast cancer and other solid cancers [18,19]. In our cohort, breast cancers with AKT1 mutations were significantly associated with positive ER-(P = 0.016) and PR (P = 0.002) but negative HER2-(P = 0.001) status.…”
Section: Discussionmentioning
confidence: 76%
“…We showed that AKT1 E17K-mutated meningiomas have a less immunosuppressive tumour microenvironment when compared to grade I NF2 meningiomas; this may explain why some NF2 tumours have high progression/recurrence rates. The molecular mechanism of how AKT1 E17K or NF2 loss influences immunosuppressive environment in the tumour is likely to involve different cell types and be more complex [39]. However, to our knowledge, this is the first time that differences in M2 macrophages in grade I meningiomas have been linked to driver mutations, and could potentially help in developing directed immunotherapies in genetically stratified meningioma patients.…”
Section: Discussionmentioning
confidence: 94%
“…The results indicated that AKT1, TP53, UBC, PTEN, and CCND1 may be pivotal targets in correlation with melanoma metastasis. Previous studies suggested that AKT1 promoted the development of melanoma metastases (Cho et al, 2015), and its melanoma-derived mutation, AKT1 E17K , activated focal adhesion kinase and promoted melanoma brain metastasis (Kircher et al, 2019). In addition, p53, encoding by TP53 gene, was reported as a therapeutic target of melanoma (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%